Green synthesis of silver nanoparticles by kyllinga brevifolia leaf extract - Nawi, Mohamad Bakhtia Mhd (Universiti Sains Malaysia, 2015)
In recent years, green chemistry and process have revealed the role of plants in biosinthesis nanoparticles. This method is an eco-friendly approach lifted in reducing the use of chemicals. This paper is a report on green synthesis of silver nanoparticles using Kyllinga brevifolia leaf extract as a reducing and stabilizing agent. The characterization of silver nanoparticles produced are Scanning Electron Microscope (SEM), Ultraviolet-visible spectroscopy (UV-VIS), Fourier Transform Infrared Spectroscopy (FTIR) and X-ray diffraction (XRD). Silver nanoparticles are produced in the form of quasi-spherical with the size depending on the variables used. Crystal properties of silver nanoparticles is face-centered cubic (FCC) oriented (111) as shown by XRD patterns. Proteins in Kyllinga brevifolia leaf extract is likely to be agents of degradation and capping agents. Kyllinga brevifolia leaf extract contains organic layers are relatively thin and washable.